Prevalence and risk factors for human leptospirosis in a rural district of Pelotas, a city in southernmost Brazil (Research, Society and Development, 2020)
Leptospirosis is one of the most widespread zoonosis in the world. In humans, the disease is responsible for more than a million cases annually. The purpose of this study was to assess human seroprevalence to leptospirosis in a rural community of southernmost Brazil. Furthermore, we assess possible epidemiological cues associated with seroprevalence. A total of 216 individuals were enrolled in the study. With an overall seroprevalence of 21.3% (n=46), to at least one of the 12 antigens tested. Seroreactivity was associated with 13 of the investigated cues, including those associated with the individuals, their behavior, environment, domestic animals, and synanthropic rodents. While seroprevalence was not particularly high when compared to other studies in similar populations, some of the risk factors associated with the disease are easy to circumvent, and indications for policymakers and future studies are made within.